2022
DOI: 10.3390/vaccines10050817
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Neutralizing Response against SARS-CoV-2 Omicron Variant in Sputnik V-Vaccinated Individuals

Abstract: The new Omicron variant of SARS-CoV-2, first identified in November 2021, is rapidly spreading all around the world. Omicron has become the dominant variant of SARS-CoV-2. There are many ongoing studies evaluating the effectiveness of existing vaccines. Studies on the neutralizing activity of vaccinated sera against the Omicron variant are currently being carried out in many laboratories. In this study, we have shown the neutralizing activity of sera against the SARS-CoV-2 Omicron variant compared to the refer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 19 publications
2
20
0
1
Order By: Relevance
“…In a study, sera were obtained from 17 people in the second week, third month, and the sixth-month post BNT162b2 programmed immunization, and their neutralization against SARS-COV 2 wild type or Omicron variant was measured by authentic virus neutralization assay. 249 It was found that the proportion of samples with neutralizing titer below the limit of detection against Omicron variants increased from 23.5% (2nd week) to 41.2% (3rd month) and 64.7% (6th month), suggesting that programmed vaccination of BNT162b could not elicit durable protection against the Omicron variant, and strengthening the necessity of booster vaccination.…”
Section: Molecular Characteristics Of Sequence and The Encoded Protei...mentioning
confidence: 97%
“…In a study, sera were obtained from 17 people in the second week, third month, and the sixth-month post BNT162b2 programmed immunization, and their neutralization against SARS-COV 2 wild type or Omicron variant was measured by authentic virus neutralization assay. 249 It was found that the proportion of samples with neutralizing titer below the limit of detection against Omicron variants increased from 23.5% (2nd week) to 41.2% (3rd month) and 64.7% (6th month), suggesting that programmed vaccination of BNT162b could not elicit durable protection against the Omicron variant, and strengthening the necessity of booster vaccination.…”
Section: Molecular Characteristics Of Sequence and The Encoded Protei...mentioning
confidence: 97%
“…The vaccine has a heterologous prime-boost regimen and is typically administered in two doses containing rAd26 as a prime and rAd5 as a boost, with a 21-day interval between the doses. The initial clinical trials demonstrated that Sputnik-V vaccination resulted in complete prevention of severe COVID-19 and was 91.6% effective against symptomatic SARS-CoV-2 infection 1 , 2 , while more recent studies indicate that the vaccine is effective against symptomatic infection by the SARS-CoV-2 variants such as delta and omicron 3 – 5 .…”
Section: Introductionmentioning
confidence: 99%
“…This lack of rigorous data has precluded major regulatory agencies and the World Health Organization from granting Sputnik-V emergency use approval 7 . The studies conducted after the original Phase I-III trials have indicated that, like the COVID-19 vaccines approved in the West, Sputnik-V is safe and elicits robust titers of binding and neutralizing antibodies (Ab) against SARS-CoV-2 5 , 8 – 21 . However, more detailed data on the reactogenicity and immunogenicity of Sputnik-V are urgently needed to not only facilitate vaccine deployment, but also to guide population-specific guidelines regarding matters such as the timing of prime-boost doses, which remains a focus of debate 19 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients, vaccinated with Sputnik V after 6-12 months, had 12 times less virus neutralizing capacity of sera against Omicron compared to original variant B.1.1.1 [16]. At the same time, those who received the vaccine from 0 to 3 months and 3 to 6 months had a virus neutralizing titer detected in 80% and 68.75% of cases, respectively [37]. In turn, the presence of previous infection and booster doses among vaccinated patients increased the proportion of people with a virus neutralizing titer against Omicron to 100% [16,37].…”
Section: Discussionmentioning
confidence: 92%
“…At the same time, those who received the vaccine from 0 to 3 months and 3 to 6 months had a virus neutralizing titer detected in 80% and 68.75% of cases, respectively [37]. In turn, the presence of previous infection and booster doses among vaccinated patients increased the proportion of people with a virus neutralizing titer against Omicron to 100% [16,37]. At the same time, it remained unclear to what extent virus neutralization correlates with field effectiveness.…”
Section: Discussionmentioning
confidence: 99%